Enamel porcelain glaze ceramic tile with metal spot bionic effect and preparation method of enamel porcelain glaze ceramic tile
By using a double-layer glaze structure and the "glaze-breaking" mechanism of black mud powder, combined with a crystalline phase composite system formed by metal oxide crystals and zircon, the problem of traditional ceramic glazes being unable to form metal inlay spots has been solved, improving the wear resistance and chemical corrosion resistance of the glaze surface and meeting the artistic and practical needs of high-end decorative scenarios.
Patent Information
- Application Number
- CN202511060450.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-10-28
AI Technical Summary
Traditional ceramic glazes cannot create the effect of metallic inlaid spots, have poor wear resistance, and are insufficient in their resistance to chemical corrosion, making it difficult to meet the needs of natural randomness and artistic feel in high-end decorative scenes.
It adopts a double-layer glaze structure, combining a metallic base glaze layer with a semi-opaque surface glaze layer. Random metallic spots are generated on the opaque substrate through the "glaze breaking" mechanism of black mud powder. The Mohs hardness and corrosion resistance of the glaze surface are improved through a composite system of metal oxide crystals with zircon, anorthite, and calcined alumina.
It achieves a three-dimensional visual effect of metallic spots, improves the wear resistance and chemical corrosion resistance of the glaze, meets the needs of mosaic application scenarios, and has a yield rate of up to 88%.
Smart Images

Figure CN120841992A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of ceramic technology, and in particular to an enamel porcelain ceramic tile with a metallic speckle biomimetic effect and its preparation method. Background Technology
[0002] Traditional ceramic glazes have significant limitations in decorative effects. Their decorative forms have long been confined to a single smooth glaze surface or a solid color tone, making it difficult to present the three-dimensional visual texture of metal inlay in enamel porcelain, and lacking the random speckled texture and light and shadow variations of inlaid metal foil. From an artistic expression perspective, traditional techniques cannot construct the multi-layered visual contrast of "opaque base + metallic spots," and the glaze surface lacks a three-dimensional sense of tactile and visual depth, making it difficult to meet the demands of high-end decorative settings for natural randomness and artistry.
[0003] In existing technologies, ceramic glazes offer limited means of achieving metallic luster, only able to achieve basic metallic tones through a single layer of glaze, and unable to create biomimetic metallic speckles similar to enamel porcelain through structural design. Furthermore, ordinary ceramic glazes suffer from poor wear resistance and insufficient resistance to chemical corrosion, failing to meet the application requirements of scenarios such as mosaics.
[0004] It is evident that existing technologies still need improvement and enhancement. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the purpose of this invention is to provide an enamel glaze ceramic tile with a metallic speckle biomimetic effect and its preparation method, aiming to solve the defects of existing glazes that cannot form a metallic inlaid speckle effect and the low hardness of existing glazes that cannot meet the application scenarios of mosaics.
[0006] To achieve the above objectives, the present invention adopts the following technical solution:
[0007] An enamel glaze ceramic tile with a metallic speckle biomimetic effect includes a base body, a metallic base glaze layer, and a semi-opaque surface glaze layer. The metallic base glaze layer is composed of either a first base glaze formula or a second base glaze formula. The first base glaze formula, by weight percentage, includes: 35-45% potassium feldspar, 10-25% quartz, 10-25% calcite, 5-15% kaolin, 2-8% talc, 2-8% zinc oxide, 10-12% iron oxide, and 5-8% manganese dioxide. The second base glaze formula, by weight percentage... The raw materials for the semi-opaque glaze layer, by mass percentage, include: 40-50% potassium feldspar, 10-20% quartz, 10-30% calcite, 5-15% kaolin, 2-8% talc, 3-6% zinc oxide, 8-10% iron oxide, and 2-5% chromium oxide; 40-45% sodium feldspar, 15-20% calcite, 10-15% talc, 2-8% calcined clay, 4-6% zircon powder, 2-4% zirconium oxide, 1-2% calcined zinc oxide, 5-15% black mud powder, and 4-5% calcined alumina.
[0008] A method for preparing an enamel glaze ceramic tile with a metallic speckle biomimetic effect as described in this invention, comprising the following steps:
[0009] The raw materials for the metal base glaze layer are fed into a ball mill according to the proportion of the first base glaze formula or the second base glaze formula. 30%-40% of the total mass of the raw materials for the metal base glaze layer is added to the ball mill to obtain the base glaze slurry.
[0010] The raw materials for the semi-opaque surface glaze are fed into a ball mill according to the formula, and 30%-40% of the total mass of the raw materials for the semi-opaque surface glaze are added. After ball milling, the surface glaze slurry is obtained.
[0011] A base glaze and a top glaze are sequentially sprayed onto the substrate using an air spraying method. The substrate with the base glaze and top glaze is then fired to produce the enamel glaze ceramic tile with a metallic speckle biomimetic effect.
[0012] The method for preparing enamel ceramic tiles with a metallic speckle biomimetic effect includes the following step: in the preparation of the base glaze slurry, alumina balls are used as the milling media, the mill speed is controlled at 180-200 r / min, and the milling time is 8-10 h until the glaze slurry has a residue of ≤0.5% after passing through a 250 mesh sieve.
[0013] The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect includes the following step: in the preparation of the surface glaze slurry, alumina balls are used as the milling media, the mill speed is controlled at 180-200 r / min, and the milling time is 12-14 h, until the glaze slurry has a residue of ≤0.5% after passing through a 250 mesh sieve.
[0014] The method for preparing enamel ceramic tiles with metallic speckle biomimetic effect includes the step of spraying a base glaze slurry onto the substrate using an air spraying method. The spray gun pressure is 0.3-0.4 MPa, the distance between the spray gun and the substrate is 15-20 cm, and the glaze is sprayed evenly until the glaze amount is 13.6-15.6 g / piece, ensuring that the thickness of the formed metallic base glaze layer is ≥0.3 mm.
[0015] The method for preparing enamel glaze ceramic tiles with metallic speckle biomimetic effect includes the step of spraying the surface glaze slurry onto the base blank using an air spraying method. The spray gun pressure is 0.2-0.3 MPa, the distance between the spray gun and the base blank is 15-20 cm, and the glaze is evenly sprayed to a weight of 15.5-17.3 g / piece.
[0016] The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect includes a firing process for the substrate with sprayed base glaze and top glaze, comprising a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 500-600℃ at a heating rate of 60℃ / min, then increased to 900-1000℃ at a heating rate of 50℃ / min, and then increased to 1200-1300℃ at a heating rate of 30-40℃ / min. In the holding stage, the temperature is held at 1200-1300℃ for 5-10 minutes. In the cooling stage, the temperature is first rapidly cooled to 800-900℃ at a cooling rate of 30-40℃ / min, and then cooled to room temperature in the furnace.
[0017] The method for preparing enamel ceramic ceramic tiles with a metallic speckle biomimetic effect, wherein the base blank is a ceramic mosaic blank.
[0018] Beneficial effects: This invention achieves a three-dimensional visual effect of randomly generated metallic spots on an opaque base through a double-layer glaze structure (metallic base glaze layer + semi-opaque top glaze layer) and a "glaze-breaking" mechanism using black mud powder. This mimics the metallic inlay texture of enamel porcelain, solving the problem of monotonous decoration in traditional glazes. Furthermore, by firing the metal oxide crystals in the base glaze layer and the zircon, anorthite, and calcined alumina in the top glaze layer to form a crystalline composite system, the Mohs hardness of the ceramic tile glaze is increased, and its wear resistance is improved by more than 30% compared to ordinary glazes. Its corrosion resistance meets national standards, making it suitable for mosaic applications. This invention also optimizes the process, reducing the impact of body color fluctuations on the glaze effect based on the double-layer glaze structure. By precisely controlling the formula ratio and firing regime, the randomness of metallic spots and batch consistency are balanced, achieving a yield rate of up to 88%. Attached Figure Description
[0019] Figure 1 This is a flowchart illustrating the preparation method of an enamel glaze ceramic tile with a metallic speckle biomimetic effect according to the present invention.
[0020] Figure 2This is a photograph of the enamel glaze ceramic tile prepared in Example 1 of the present invention.
[0021] Figure 3 This is a photograph of the enamel porcelain ceramic tile prepared in Example 2 of the present invention.
[0022] Figure 4 This is a photograph of the enamel porcelain ceramic tile prepared in Example 3 of the present invention.
[0023] Figure 5 This is a physical image of the ceramic tile prepared in Comparative Example 1 of the present invention.
[0024] Figure 6 This is a physical image of the ceramic tile prepared in Comparative Example 3 of the present invention. Detailed Implementation
[0025] This invention provides an enamel glaze ceramic tile with a metallic speckle biomimetic effect and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following embodiments are provided to further illustrate the invention in detail. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0026] This invention provides an enamel glaze ceramic tile with a metallic speckle biomimetic effect, comprising a base body, a metallic base glaze layer, and a semi-opaque surface glaze layer. The metallic base glaze layer is composed of either a first base glaze formula or a second base glaze formula. The first base glaze formula, by weight percentage, comprises: 35-45% potassium feldspar, 10-25% quartz, 10-25% calcite, 5-15% kaolin, 2-8% talc, 2-8% zinc oxide, 10-12% iron oxide, and 5-8% manganese dioxide. The second base glaze formula, by weight percentage... The raw materials for the semi-opaque glaze layer, by mass percentage, include: potassium feldspar 40-50%, quartz 10-20%, calcite 10-30%, kaolin 5-15%, talc 2-8%, zinc oxide 3-6%, iron oxide 8-10%, and chromium oxide 2-5%; the raw materials for the semi-opaque glaze layer, by mass percentage, include: sodium feldspar 40-45%, calcite 15-20%, talc 10-15%, calcined clay 2-8%, zircon powder 4-6%, oriental zircon 2-4%, calcined zinc oxide 1-2%, black mud powder 5-15%, and calcined alumina 4-5%.
[0027] Specifically, the metallic base coat contains two formulations. The first base coat formulation is a coffee gold / bronze metallic base coat, which, by mass percentage, includes: 35-45% potassium feldspar, 10-25% quartz, 10-25% calcite, 5-15% kaolin, 2-8% talc, 2-8% zinc oxide, 10-12% iron oxide, and 5-8% manganese dioxide. This formulation can form a uniform metallic luster base at high temperatures. Iron oxide, as the main colorant, provides a gold / brown tone. Manganese dioxide works synergistically with iron oxide to deepen the color and promote metallic luster and iridescent effects. In this formula, iron oxide is the main colorant. When its content is 10-12%, it forms a good metallic luster. Below 10%, the color is too light, the metallic feel is weak, and the yield decreases. If it exceeds 12%, the glaze is prone to blackening, and the gas generated by high-temperature decomposition increases the risk of pinholes, further reducing the yield. Manganese dioxide works synergistically with iron. The optimal dosage is 5-8%, which promotes metallic luster and iridescent effect. If it exceeds 8%, the melting temperature of the glaze decreases, which can easily lead to glaze flow, covering metallic spots, and reducing the yield.
[0028] The second base glaze formula is a red-gold / rust-red metallic base glaze, which, by weight percentage, includes: 40-50% potassium feldspar, 10-20% quartz, 10-30% calcite, 5-15% kaolin, 2-8% talc, 3-6% zinc oxide, 8-10% iron oxide, and 2-5% chromium oxide. In this formula, chromium oxide reacts with iron to form a reddish-brown hue with a metallic sheen, significantly enhancing the metallic texture. By precisely controlling the proportions of each component, a metallic sheen ranging from red-gold and rust-red to dark brown can be produced. In this formula, chromium oxide plays a crucial role in the iron-chromium base glaze at a dosage of 2-5%, forming a reddish-brown hue with a metallic sheen. If the dosage exceeds 5%, the glaze surface becomes dry, the color becomes too dark and black, and Cr may precipitate. 6+ It affects environmental friendliness and reduces the yield; the best effect of promoting gloss and crystallization is achieved when the zinc oxide (ZnO) dosage is 3-6%; if it exceeds 6%, the glaze becomes opaque and the metallic effect is weakened; if it is below 3%, the glaze gloss decreases, all of which affect the yield.
[0029] The raw materials for the semi-opaque glaze layer, by mass percentage, include: 40-45% albite, 15-20% calcite, 10-15% talc, 2-8% calcined clay, 4-6% zircon powder, 2-4% zirconium silicate, 1-2% calcined zinc oxide, 5-15% black mud powder, and 4-5% calcined alumina. In this formula, the dual zirconium sources (zircon powder and zirconium silicate) work synergistically to enhance the covering power by precipitating ZrSiO4 crystals. Zirconium silicate refers to artificially synthesized zirconium silicate prepared from zircon powder. Black mud powder, as a key raw material for "glaze breaking," is rich in Fe2O3, which reacts locally at high temperatures to form "breaks," exposing the underlying metallic glaze. Calcined alumina can improve the hardness and wear resistance of the glaze, while calcite ensures a low melting temperature and good fluidity of the glaze, resulting in an opaque effect. Specifically, a sodium feldspar ratio of 40-45% ensures a low melting temperature and good fluidity for the glaze, creating an opaque effect. Below 40%, the opaque effect is poor, and the covering power is insufficient. Above 45%, the high-temperature viscosity decreases, making it prone to flowing and covering metallic spots, resulting in a lower yield. A zircon powder + oriental zirconium content of 6-10% provides a stable opaque effect. Below 6%, the opacity is insufficient, and the substrate is translucent. Above 10%, the glaze hardness increases but the toughness decreases, making it prone to cracking and reducing the yield. In this formula, the amount of black mud powder is 5-15%, which forms metallic spots through "glaze breaking." Below 5%, the "glaze breaking" effect is weak, and there are few metallic spots. Above 15%, it easily generates a large amount of gas, leading to pinholes, bubbles, and defects, resulting in a lower yield. The amount of calcined alumina is 4-5%, balancing hardness and fluidity. Above 5%, the high-temperature viscosity increases significantly, the glaze melts insufficiently, and the surface is rough. Below 4%, the wear resistance decreases, affecting the yield.
[0030] This invention is the first to create a clear layered structure of a metallic base glaze (metallic effect) and a semi-opaque top glaze (covering and modification), which is different from the traditional single-layer or mixed glaze structure. This layered design allows the luster of the metallic base glaze and the opaque effect of the top glaze to complement each other. Through the "glaze breaking" mechanism of black mud powder in the semi-opaque top glaze, the random distribution of metallic spots on the opaque base is achieved, forming a unique visual effect.
[0031] This invention generates irregular metallic spots through the synergistic reaction between the surface glaze black mud powder and the metal base glaze layer, successfully simulating the effect of metal foil inlay in enamel porcelain; the local reaction of Fe2O3 in the black mud powder at high temperature causes the surface glaze layer to become locally thinner or form holes, revealing the underlying metal base glaze and forming metallic spots with natural randomness, avoiding a mechanical feel and embodying the artistic essence of handmade enamel.
[0032] The metal oxide crystals in the metal base glaze layer, together with the zircon, anorthite, calcined alumina, etc. in the semi-opaque surface glaze layer, form a crystalline composite system after firing. This system makes the glaze surface have a high Mohs hardness and improved wear resistance compared to ordinary glazes. At the same time, it enhances the resistance to chemical corrosion and meets the durability requirements of mosaic application scenarios.
[0033] By adjusting the frit ratio in the metallic base glaze layer, various metallic tones such as gold, silver, and copper can be presented. The semi-opaque surface glaze layer can achieve various base colors such as green and cloisonné through colorants, realizing flexible and adjustable color. This color control capability provides the product with rich artistic expression and meets the needs of different decorative scenarios.
[0034] In some embodiments, a method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect, as described in this invention, is also provided. Figure 1 As shown, it includes the following steps:
[0035] S10. The raw materials of the metal base glaze layer are put into a ball mill according to the proportion of the first base glaze formula or the second base glaze formula, and 30%-40% of the total mass of the raw materials of the metal base glaze layer is added. After ball milling, the base glaze slurry is obtained.
[0036] S20. The raw materials of the semi-opaque surface glaze are put into a ball mill according to the formula, and 30%-40% of the total mass of the raw materials of the semi-opaque surface glaze is added. After ball milling, the surface glaze slurry is obtained.
[0037] S30. Using an air spraying method, a base glaze slurry and a top glaze slurry are sprayed sequentially onto the base blank. Then, the base blank with the sprayed base glaze slurry and top glaze slurry is fired to obtain the enamel porcelain glaze ceramic tile with the metallic speckle biomimetic effect.
[0038] Specifically, in the preparation of the base glaze slurry, the raw materials for the metal base glaze layer are fed into a ball mill according to the proportion of the first or second base glaze formula. Deionized water, accounting for 30%-40% of the total mass of the raw materials, is added. Alumina balls are used as the milling media. The ball mill speed is controlled at 180-200 r / min, and the milling time is 8-10 hours, until the glaze slurry has a residue of ≤0.5% on a 250-mesh sieve, ensuring fine particles. Finally, the specific gravity of the base glaze slurry is adjusted to 1.55-1.6 g / cm³ by adding water or other raw materials. 3 .
[0039] In the preparation of the surface glaze slurry, the raw materials for the semi-opaque surface glaze layer are fed into a ball mill according to the formula. Deionized water, accounting for 30%-40% of the total mass of the raw materials for the semi-opaque surface glaze layer, is added. Alumina balls are used as the milling media. The ball mill speed is controlled at 180-200 r / min, and the milling time is 12-14 h, until the glaze slurry passes through a 250-mesh sieve with a residue of ≤0.5%. This ensures that difficult-to-grind raw materials such as zircon powder are fully dispersed, improving the uniformity of the glaze slurry. The specific gravity of the surface glaze slurry is adjusted to 1.6-1.7 g / cm³ by adding water or other raw materials. 3 Meanwhile, the suspension of the glaze slurry was observed, and the suspension was improved by adding an appropriate amount of CMC (carboxymethyl cellulose) to prevent the glaze slurry from settling.
[0040] In the step of applying the base glaze slurry to the substrate using the air spraying method, a porcelain mosaic substrate (45mm×300mm×8mm) is selected. The substrate must be dry, clean, and free of cracks and impurities. The base glaze slurry is applied using the air spraying method with a spray gun pressure of 0.3-0.4MPa and a distance of 15-20cm from the substrate. The glaze is sprayed evenly to a thickness of 13.6-15.6g / substrate, ensuring a metallic base glaze layer thickness ≥0.3mm and uniform coverage. In this step, a glaze thickness of 13.6-15.6g / substrate results in a suitable thickness, uniform metallic luster, and a yield of 85%. If the glaze thickness is less than 13.6g / substrate, the glaze layer is too thin, resulting in a weak metallic sheen; if the glaze thickness is greater than 15.6g / substrate, the glaze layer is too thick and prone to cracking, reducing the yield.
[0041] In the step of applying the top glaze slurry to the substrate using the air spraying method, the spray gun pressure should be 0.2-0.3 MPa to avoid the glaze layer being too thick or too thin, ensuring good adhesion between the top glaze and the base glaze. The spray gun should be 15-20 cm away from the substrate, and the glaze should be sprayed evenly to a thickness of 15.5-17.3 g / piece. In this step, when the glaze thickness is 15.5-17.3 g / piece, the thickness is moderate, and the yield is 88%. If the glaze thickness is less than 15.5 g / piece, the metallic specks will be small and transparent to the substrate; if the glaze thickness is greater than 17.3 g / piece, the metallic specks will be covered, and the yield will decrease.
[0042] The firing process for the blanks coated with base glaze and top glaze includes a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 500-600℃ at a rate of 60℃ / min, then to 900-1000℃ at a rate of 50℃ / min, and finally to 1200-1300℃ at a rate of 30-40℃ / min. This gradual heating prevents cracking of the blank and glaze due to thermal stress. In the holding stage, the temperature is held at 1200-1300℃ for 5-10 minutes to ensure complete melting of the glaze and full crystal development. In the cooling stage, the temperature is first rapidly cooled to 800-900℃ at a rate of 30-40℃ / min, and then cooled to room temperature in the furnace. The cooling rate is controlled to obtain good metallic luster and glaze surface properties. In this step, segmented heating can avoid thermal stress cracks in the body and glaze, maintaining a yield of approximately 88%. If the heating rate exceeds 60℃ / min, it will cause rapid evaporation of moisture inside the body, easily leading to blistering and a decrease in yield. In this embodiment, the holding time during the heat preservation stage is 5-10 minutes to ensure that the glaze is fully melted and the crystals are fully developed, achieving a yield of 88%. If it is less than 5 minutes, the glaze may not melt sufficiently, resulting in a rough surface; if it is more than 10 minutes, the glaze will over-melt and easily flow, reducing the yield. In this embodiment, the holding temperature is 1200-1300℃, which allows the base glaze metal oxides to fully crystallize, exhibiting a uniform metallic luster. The top glaze is completely melted, the opaque base is smooth, and the metal spots are clear and randomly distributed without obvious defects, achieving a yield of up to 88%. If the temperature is below 1200℃, the base glaze is not fully melted, the metal oxide crystallization is insufficient, the luster is weak, the color is dark, the top glaze is not fully melted, the opaque effect is poor, the base is translucent, and the base and top glazes are not tightly bonded, making them easy to peel off. The edges of the metal spots are blurred, reducing the yield to about 70%. If the temperature is above 1300℃, the base glaze is over-melted, the metal crystals decompose, the luster diminishes, the top glaze becomes too fluid, excessively covering the metal spots, resulting in blurred spots, severe glaze flow, transparent edges, and an uneven glaze surface, reducing the yield to about 75%. In this embodiment, rapid cooling to 800-900℃ at a cooling rate of 30-40℃ / min during the cooling stage effectively locks in the metal crystal morphology and inhibits the glaze flow from covering the spots.
[0043] The enamel glaze ceramic tile prepared by this invention has a base layer of metallic glaze, which precipitates metallic crystals at high temperature to form a glossy base. Its surface layer is a semi-opaque glaze layer, which achieves opacity through zircon crystals (ZrSiO4). The black mud powder in the semi-opaque glaze layer partially decomposes at 1200-1300℃, generating gas and compositional changes, forming micropores or melting differences, causing the underlying metallic glaze to appear as random spots. This invention employs an air spraying method for glazing, achieving uniform glazing of both the base and top glazes by controlling different spraying pressures and glaze amounts. Precise control of firing temperature and holding time ensures sufficient melting of the glaze and good crystal development, improving product consistency and stability.
[0044] The present invention will be further explained and illustrated below through specific embodiments:
[0045] Example 1
[0046] An enamel glaze ceramic tile with a metallic speckle biomimetic effect includes a base body, a metallic base glaze layer, and a semi-opaque top glaze layer. The metallic base glaze layer is composed of a first base glaze formula, which, by weight percentage, comprises: 40% potassium feldspar, 15% quartz, 15% calcite, 5% kaolin, 5% talc, 3% zinc oxide, 11% iron oxide, and 6% manganese dioxide. The semi-opaque top glaze layer, by weight percentage, comprises: 43% sodium feldspar, 17% calcite, and 4% talc. The ingredients are: 11% stone, 5% calcined clay, 5% zircon powder, 3% oriental zircon, 1.5% calcined zinc oxide, 10% black mud powder, and 4.5% calcined alumina. It should be noted that different colored pigments are added to the semi-opaque glaze layer to achieve different colors on the tile surface. The addition of pigments does not affect the metallic effect, and the amount of pigment is not included in the raw materials of the semi-opaque glaze layer. In this embodiment, 0.8% peacock blue and 1.5% peacock green, accounting for 1.8% of the total raw materials, are added to the semi-opaque glaze layer. The preparation method includes the following steps:
[0047] The raw materials for the metallic base glaze layer were fed into a ball mill according to the proportions of the first base glaze formula. Deionized water, accounting for 35% of the total mass of the raw materials, was added. Alumina balls were used as the milling media. The ball mill speed was controlled at 200 r / min, and the milling time was 9 hours, until the glaze slurry showed a residue of ≤0.5% on a 250-mesh sieve, ensuring fine particles. Finally, the specific gravity of the base glaze slurry was adjusted to 1.57 g / cm³ by adding water or other raw materials. 3 The base glaze slurry was prepared.
[0048] The raw materials for the semi-opaque glaze layer are fed into a ball mill according to the formula. Deionized water, accounting for 35% of the total mass of the raw materials, is added. Alumina balls are used as the milling media. The ball mill speed is controlled at 200 r / min, and the milling time is 13 hours, until the glaze slurry passes through a 250-mesh sieve with a residue of ≤0.5%. This ensures that difficult-to-grind raw materials such as zircon powder are fully dispersed, improving the uniformity of the glaze slurry. The specific gravity of the glaze slurry is adjusted to 1.65 g / cm³ by adding water or other raw materials. 3 The surface glaze slurry is then prepared.
[0049] The base glaze slurry is applied to the substrate using an air spraying method. A ceramic mosaic substrate (45mm×300mm×8mm) is selected. The substrate must be dry, clean, and free of cracks and impurities. The base glaze slurry is applied using an air spraying method with a spray gun pressure of 0.4MPa and a spray gun distance of 20cm from the substrate. The glaze is sprayed evenly to a thickness of 14.5g / piece, ensuring that the resulting metallic base glaze layer is ≥0.3mm thick and that the base glaze is evenly covered.
[0050] The top glaze is then sprayed onto the base glaze using an air spraying method. The spray gun pressure is 0.3 MPa to avoid the glaze layer being too thick or too thin, ensuring good adhesion between the top glaze and the base glaze. The spray gun is 20 cm away from the biscuit, and the glaze is sprayed evenly until the glaze amount is 16.5 g / piece.
[0051] The firing process for the blanks coated with base glaze and top glaze includes a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 600℃ at a rate of 60℃ / min, then to 1000℃ at a rate of 50℃ / min, and then to 1250℃ at a rate of 35℃ / min. This gradual heating avoids cracking of the blank and glaze due to thermal stress. In the holding stage, the temperature is held at 1250℃ for 10 minutes to ensure that the glaze is fully melted and the crystals are fully developed. In the cooling stage, the temperature is first rapidly cooled to 900℃ at a rate of 35℃ / min, and then cooled to room temperature in the furnace. The cooling rate is controlled to obtain good metallic luster and glaze performance.
[0052] The enamel glaze ceramic tile prepared in Example 1 is as follows: Figure 2 As shown, its glaze exhibits a uniform bronze metallic luster, with a distinct iridescent effect and evenly distributed metallic spots.
[0053] The hardness of the enamel ceramic tile surface in Example 1 was tested using a Mohs hardness tester. Five points were tested on each sample, and the average value was taken. The Mohs hardness was found to be 7.
[0054] Example 2
[0055] An enamel glaze ceramic tile with a metallic speckle biomimetic effect includes a base body, a metallic base glaze layer, and a semi-opaque surface glaze layer. The metallic base glaze layer is composed of a second base glaze formula, which, by weight percentage, comprises: 45% potassium feldspar, 15% quartz, 10% calcite, 8% kaolin, 5% talc, 5% zinc oxide, 9% iron oxide, and 3% chromium oxide. The semi-opaque surface glaze layer, by weight percentage, comprises: 45% sodium feldspar, 20% calcite, 10% talc, 5% calcined clay, 4% zircon powder, 4% oriental zircon, 1% calcined zinc oxide, 6% black mud powder, and 5% calcined alumina. In this embodiment, praseodymium yellow, accounting for 0.12% of the total raw materials of the semi-opaque surface glaze layer, is also added. The preparation method is the same as in Example 1.
[0056] The enamel glaze ceramic tile prepared in Example 2 is as follows: Figure 3 As shown, its glaze forms bright rust-red metallic spots, and the addition of chromium significantly enhances the metallic texture.
[0057] The hardness of the enamel ceramic tile surface in Example 2 was tested using a Mohs hardness tester. Five points were tested on each sample, and the average value was taken. The Mohs hardness was found to be 8.
[0058] Example 3
[0059] An enamel ceramic tile with a metallic speckle biomimetic effect includes a base body, a metallic base glaze layer, and a semi-opaque surface glaze layer. The metallic base glaze layer is composed of a first base glaze formula, which, by weight percentage, comprises: 45% potassium feldspar, 20% quartz, 10% calcite, 5% kaolin, 2% talc, 2% zinc oxide, 10% iron oxide, and 6% manganese dioxide. The semi-opaque surface glaze layer, by weight percentage, comprises: 40% sodium feldspar, 15% calcite, 15% talc, 2% calcined clay, 6% zircon powder, 2% oriental zirconium, 2% calcined zinc oxide, 14% black mud powder, and 4% calcined alumina. In this embodiment, vanadium zirconium blue (1.38% of the total raw materials used in the semi-opaque surface glaze layer) and praseodymium yellow (2.12%) are also added to the semi-opaque surface glaze layer. The preparation method is the same as in Example 1.
[0060] The enamel glaze ceramic tile prepared in Example 3 is as follows: Figure 4 As shown, its glaze forms a bronze metallic luster, and the total amount of dual zirconium sources in the glaze is 8%, resulting in the best opacity effect, which can effectively cover the body and base glaze colors, and the metallic spots have good randomness and clarity.
[0061] The hardness of the enamel ceramic tile surface in Example 3 was tested using a Mohs hardness tester. Five points were tested on each sample, and the average value was taken. The Mohs hardness was found to be 7.
[0062] Comparative Example 1
[0063] A ceramic tile includes a base, a metallic base glaze layer, and a semi-opaque top glaze layer. The metallic base glaze layer comprises a first base glaze formula, which, by weight percentage, includes: 40% potassium feldspar, 15% quartz, 15% calcite, 5% kaolin, 5% talc, 3% zinc oxide, 11% iron oxide, and 6% manganese dioxide. The semi-opaque top glaze layer, by weight percentage, comprises: 43% sodium feldspar, 20% calcite, 14% talc, 5% calcined clay, 5% zircon powder, 3% zirconium oxide, 1.5% calcined zinc oxide, 4% black mud powder, and 4.5% calcined alumina. In this comparative example, vanadium zirconium blue, accounting for 1.4% of the total raw materials used in the semi-opaque top glaze layer, is also added. The preparation method is the same as in Example 1.
[0064] The ceramic tiles prepared in Comparative Example 1 are as follows Figure 5 As shown, in this comparative example, due to the small amount of black mud powder used, the metal spots were sparse, and the yield was reduced to about 60%.
[0065] Comparative Example 2
[0066] A ceramic tile includes a base, a metallic base glaze layer, and a semi-opaque top glaze layer. The metallic base glaze layer is composed of a first base glaze formula, which, by mass percentage, comprises: 40% potassium feldspar, 15% quartz, 15% calcite, 5% kaolin, 5% talc, 3% zinc oxide, 11% iron oxide, and 6% manganese dioxide. The semi-opaque top glaze layer, by mass percentage, comprises: 40% sodium feldspar, 15% calcite, 10% talc, 5% calcined clay, 5% zircon powder, 3% zirconium oxide, 1.5% calcined zinc oxide, 16% black mud powder, and 4.5% calcined alumina. Its preparation method is the same as in Example 1.
[0067] In Comparative Example 2, the excessive use of black mud powder led to an increase in pinhole defects on the glaze surface, reducing the yield to approximately 55%.
[0068] Comparative Example 3
[0069] A ceramic tile includes a base, a metallic base glaze layer, and a semi-opaque top glaze layer. The metallic base glaze layer is composed of a first base glaze formula, which, by weight percentage, comprises: 43% potassium feldspar, 15% quartz, 15% calcite, 5% kaolin, 5% talc, 3% zinc oxide, 8% iron oxide, and 6% manganese dioxide. The semi-opaque top glaze layer, by weight percentage, comprises: 45% sodium feldspar, 20% calcite, 10% talc, 5% calcined clay, 4% zircon powder, 4% oriental zircon, 1% calcined zinc oxide, 6% black mud powder, and 5% calcined alumina. In this comparative example, 0.18% cobalt black and 0.66% golden brown, accounting for 0.18% of the total raw materials used in the semi-opaque top glaze layer, are also added. The preparation method is the same as in Example 1.
[0070] The ceramic tiles prepared in Comparative Example 3 are as follows Figure 6 As shown, in Comparative Example 3, the color was too light and the metallic feel was weak because the amount of iron oxide in the first base glaze formula was too small.
[0071] Comparative Example 4
[0072] A ceramic tile includes a base, a metallic base glaze layer, and a semi-opaque top glaze layer. The metallic base glaze layer comprises a first base glaze formula, which, by mass percentage, includes: 38% potassium feldspar, 15% quartz, 15% calcite, 5% kaolin, 5% talc, 3% zinc oxide, 13% iron oxide, and 6% manganese dioxide. The semi-opaque top glaze layer, by mass percentage, comprises: 40% sodium feldspar, 15% calcite, 15% talc, 2% calcined clay, 6% zircon powder, 2% zirconium oxide, 2% calcined zinc oxide, 14% black mud powder, and 4% calcined alumina. Its preparation method is the same as in Example 1.
[0073] The ceramic tile prepared in Comparative Example 4 had an excessive amount of iron oxide in the first base glaze formula, which caused the glaze surface to easily turn black and increased the risk of pinholes, resulting in a yield of approximately 72%.
[0074] Comparative Example 5
[0075] An enamel glaze ceramic tile with a metallic speckle biomimetic effect includes a base body, a metallic base glaze layer, and a semi-opaque surface glaze layer. The metallic base glaze layer is composed of a second base glaze formula, which, by mass percentage, comprises: 45% potassium feldspar, 17% quartz, 10% calcite, 8% kaolin, 5% talc, 5% zinc oxide, 9% iron oxide, and 1% chromium oxide. The semi-opaque surface glaze layer, by mass percentage, comprises: 45% sodium feldspar, 20% calcite, 10% talc, 5% calcined clay, 4% zircon powder, 4% oriental zircon, 1% calcined zinc oxide, 6% black mud powder, and 5% calcined alumina. Its preparation method is the same as in Example 1.
[0076] The ceramic tile prepared in Comparative Example 5 had a weak metallic texture due to insufficient chromium oxide in the second base glaze formula, and the yield was approximately 75%.
[0077] Comparative Example 6
[0078] A ceramic tile includes a base, a metallic base glaze layer, and a semi-opaque top glaze layer. The metallic base glaze layer is composed of a second base glaze formula, which, by mass percentage, comprises: 42% potassium feldspar, 15% quartz, 10% calcite, 8% kaolin, 5% talc, 5% zinc oxide, 9% iron oxide, and 6% chromium oxide. The semi-opaque top glaze layer, by mass percentage, comprises: 45% sodium feldspar, 20% calcite, 10% talc, 5% calcined clay, 4% zircon powder, 4% oriental zircon, 1% calcined zinc oxide, 6% black mud powder, and 5% calcined alumina. Its preparation method is the same as in Example 1.
[0079] The ceramic tile prepared in Comparative Example 6 has an excessive amount of chromium oxide in the second base glaze formula, resulting in a dry glaze surface, an overly dark and black color, and a yield of approximately 73%.
[0080] Comparative Example 7
[0081] An enamel ceramic tile with a metallic speckle biomimetic effect includes a base, a metallic base glaze layer, and a semi-opaque surface glaze layer. The raw material composition of the metallic base glaze layer and the semi-opaque surface glaze layer are the same as those in Example 1. The preparation method is the same as that in Example 1, except that the heat preservation temperature is changed to 1100℃.
[0082] In Comparative Example 7, the base glaze was not completely melted due to the low heat preservation temperature, resulting in a weak metallic luster and a yield of approximately 70%.
[0083] Comparative Example 8
[0084] An enamel ceramic tile with a metallic speckle biomimetic effect includes a base, a metallic base glaze layer, and a semi-opaque surface glaze layer. The raw material composition of the metallic base glaze layer and the semi-opaque surface glaze layer are the same as those in Example 1. The preparation method is the same as that in Example 1, except that the heat preservation temperature is changed to 1400℃.
[0085] In Comparative Example 8, the excessive heat preservation temperature caused the glaze to flow excessively, covering the metal points, resulting in a yield of approximately 75%.
[0086] In summary, the metallic base glaze layer of this invention is mainly composed of potassium feldspar and quartz, combined with calcite and kaolin, forming a uniform glassy phase substrate at high temperature. Zinc oxide and talc regulate the melting temperature, and metal oxides such as iron oxide serve as crystallization sources, giving the glaze a metallic luster. The semi-opaque surface glaze layer uses albite as a flux, and zircon powder and oriental zircon create an opaque effect. The high-temperature decomposition of black mud powder exposes the metallic base glaze, and firing zinc oxide and other materials enhances the glaze performance. Firing clay ensures uniform glazing. In terms of process, controlling the firing temperature and holding time promotes crystal development and black mud powder reaction, segmented temperature rise and fall prevent cracking and lock the crystal morphology, and the glaze thickness and fluidity are controlled according to the specific gravity and viscosity of the glaze. Air spraying at different pressures is used to construct a double-layer glaze structure. The synergistic effect of various parameters achieves the biomimetic presentation of metallic spots, the visual layering of the opaque substrate, and the enhancement of glaze performance.
[0087] It is understood that those skilled in the art can make equivalent substitutions or modifications to the technical solution and inventive concept of the present invention, and all such substitutions or modifications should fall within the protection scope of the appended claims.
Claims
1. An enamel porcelain ceramic tile with a metallic speckle biomimetic effect, comprising a base, a metallic base glaze layer, and a semi-opaque surface glaze layer, characterized in that, The raw material composition of the metallic base glaze layer is either a first base glaze formula or a second base glaze formula. The first base glaze formula, by mass percentage, includes: 35-45% potassium feldspar, 10-25% quartz, 10-25% calcite, 5-15% kaolin, 2-8% talc, 2-8% zinc oxide, 10-12% iron oxide, and 5-8% manganese dioxide. The second base glaze formula, by mass percentage, includes: 40-50% potassium feldspar and 10-20% quartz. The raw materials for the semi-opaque glaze layer, by mass percentage, include: 10-30% calcite, 5-15% kaolin, 2-8% talc, 3-6% zinc oxide, 8-10% iron oxide, and 2-5% chromium oxide; 40-45% albite, 15-20% calcite, 10-15% talc, 2-8% calcined clay, 4-6% zircon powder, 2-4% zirconium oxide, 1-2% calcined zinc oxide, 5-15% black mud powder, and 4-5% calcined alumina.
2. A method for preparing an enamel glaze ceramic tile with a metallic speckle biomimetic effect as described in claim 1, characterized in that, Including the following steps: The raw materials for the metal base glaze layer are fed into a ball mill according to the proportion of the first base glaze formula or the second base glaze formula. 30%-40% of the total mass of the raw materials for the metal base glaze layer is added to the ball mill to obtain the base glaze slurry. The raw materials for the semi-opaque surface glaze are fed into a ball mill according to the formula, and 30%-40% of the total mass of the raw materials for the semi-opaque surface glaze are added. After ball milling, the surface glaze slurry is obtained. A base glaze and a top glaze are sequentially sprayed onto the substrate using an air spraying method. The substrate with the base glaze and top glaze is then fired to produce the enamel glaze ceramic tile with a metallic speckle biomimetic effect.
3. The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect according to claim 2, characterized in that, In the step of preparing the base glaze slurry, alumina balls are used as the ball milling media, the ball mill speed is controlled at 180-200 r / min, and the ball milling time is 8-10 h, until the glaze slurry passes through a 250 mesh sieve with a residue of ≤0.5%.
4. The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect according to claim 2, characterized in that, In the step of preparing the glaze slurry, alumina balls are used as the milling media, the mill speed is controlled at 180-200 r / min, and the milling time is 12-14 h until the glaze slurry passes through a 250 mesh sieve with a residue of ≤0.5%.
5. The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect according to claim 2, characterized in that, In the step of applying the base glaze slurry to the blank using the air spraying method, the spray gun pressure is 0.3-0.4MPa, the spray gun distance from the blank is 15-20cm, and the glaze is evenly sprayed to a glaze amount of 13.6-15.6g / piece, ensuring that the thickness of the formed metallic base glaze layer is ≥0.3mm.
6. The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect according to claim 2, characterized in that, In the step of applying the top glaze slurry to the blank using the air spraying method, the spray gun pressure is 0.2-0.3MPa, the distance between the spray gun and the blank is 15-20cm, and the glaze is evenly sprayed to a weight of 15.5-17.3g / piece.
7. The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect according to claim 2, characterized in that, The firing process for the substrate with sprayed base glaze and top glaze includes a heating stage, a holding stage, and a cooling stage. In the heating stage, the temperature is increased to 500-600℃ at a heating rate of 60℃ / min, then increased to 900-1000℃ at a heating rate of 50℃ / min, and then increased to 1200-1300℃ at a heating rate of 30-40℃ / min. In the holding stage, the temperature is held at 1200-1300℃ for 5-10 minutes. In the cooling stage, the temperature is first rapidly cooled to 800-900℃ at a cooling rate of 30-40℃ / min, and then cooled to room temperature in the furnace.
8. The method for preparing enamel glaze ceramic tiles with a metallic speckle biomimetic effect according to claim 2, characterized in that, The blank is a ceramic mosaic blank.
Citation Information
Cited By
Steel plate enamel high-temperature matte glaze free of fluoride salt and nitrate as well as preparation method and application of steel plate enamel high-temperature matte glaze
CN121159100A
Medium-temperature semitransparent glaze for steel plate enamel without fluoride salt and nitrate as well as preparation method and application of medium-temperature semitransparent glaze
CN121159117A
Cast iron enamel semitransparent glaze free of fluoride salt and nitrate as well as preparation method and application of cast iron enamel semitransparent glaze
CN121159127A
Black-matrix golden ceramic painting material based on hawksbill glaze color development, and preparation and firing methods thereof
CN121929910A